Efektifitas Sprint Interval Training (SIT) dalam Meningkatkan VO2max Pemain Sepak Bola - Hernandi, Iman Budi; Pamungkas, Hari; Sudarsono, Sudarsono; Kurniawan, Rubbi (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2024)
VO2max is a component that affects the performance of a soccer player on the field. Research was conducted to examine the extent to which SIT can provide significant benefits in increasing VO2max for soccer players. The study used a quasi-experiment with a quantitative approach. The samples involved were Persikab Bandung soccer players in 2023 as many as 18 players who were given treatment in the form of Sprint Interval Training (SIT). The instrument uses the MFT (Multistage Fitness Test) which is used to measure the player's VO2max. The results showed that the average VO2max before treatment was 48,678 ± 7,883, and the average VO2max after training was 51,417 ± 4,944. Based on the results of the analysis, it is concluded that Sprint Interval Training (SIT) can effectively increase the VO2max capacity of soccer players. The results of this study are expected to contribute to the development of football training programs.